Pengaruh Jenis Kemasan Terhadap Karakteristik Teh Herbal Daun Bambu Tabah (Gigantochloa nigrociliata Buse-Kurz) Selama Penyimpanan - Maria Elfira Semana; Pande Ketut Diah Kencana; I Gusti Ngurah Apriadi Aviantara (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2021)
The purpose of the study was to determine the packaging that maintain the quality characteristics contained in tabah bamboo leaf herbal tea with packaging treatment using threes different types of packaging stored in an incubator with a temperature of 30°C ± 3°C with a storage time of 42 days. This study used a completely randomized design (CRD) which consisted of two factors, namely the use of different types of packaging and storage time and three replications. The first factor consists of three levels, namely, (K1): Aluminum Foil, (K2): Polypropylene Plastic (PP), and (K3): Paper Sack. The second factor consists of three levels, namely, (T1): 14 days of storage, (T2): 28 days of storage, and (T3): 42 days of storage. The parameters observed in the study consisted of moisture content, pH, total acid, total phenol, total flavonoids, and organoleptic tests consisting of color, aroma, and taste of brewed tabah bamboo tea leaves. The results showed that the highest phenol content was found in the treatment of using aluminum foil packaging for 42 days, which was 119,354 mg / 100g and the highest or best total flavonoids were found in the treatment of using aluminum foil packaging for 42 days, namely 27,419 mg / 100g.